Hubungan Antara Attachment Style dan Interpersonal Trust dalam Pengerjaan Tugas Kelompok Mahasiswa - Nabila Aulia Dwi Cahya; Debora Basaria (Universitas Darul Ulum, 2026)
This study aims to examine the relationship between attachment style and interpersonal trust among university students working on group assignments. A quantitative approach with a correlational design was employed. The participants were 324 students aged 18–25 years who had prior experience working in groups. Data were collected using Adult Attachment Style (AAS) and Interpersonal Trust Scale (ITS) that had undergone adaptation and reliability testing. Data analysis was conducted using parametric statistical techniques to identify the relationship between the variables. The results indicate a positive relationship between attachment style and interpersonal trust in the context of group work. These findings suggest that attachment patterns play a role in shaping students’ tendencies to trust their peers during collaborative tasks. This study highlights the importance of relational factors in supporting effective group work and provides a foundation for developing learning strategies that enhance positive interpersonal interactions.